South Africa's negotiated transition from apartheid to an inclusive political system: what capitalist interests reigned supreme? - Shivambu, Nyiko Floyd (My University, 2015)
South Africa’s negotiated transition from apartheid to an electorally inclusive political has many interpretations, because it was contested by various classes, strata and fractions of capital. Like all capitalist states, the apartheid state was a contested state, whose policy direction and ultimate reformation was contested not only by the contending classes in a capitalist system, by fractions of capital within the dominant and ruling class. As a result, mining, finance and aspirant black capitalist interests reigned supreme over the transition from apartheid to an inclusive political system and notably reigned supreme over the ANC-led liberation movement’s economic aspirations. This is reflected in the structural socio-economic problems of inequalities, unemployment, under-employment and therefore poverty which preceded and succeed the ‘end of apartheid’. Failure to comprehend this phenomenon will be disastrous for future economic policy making, because from all ideological and political streams, there should be a recognition in South African political economy that massive labour absorptive industrial development and expansion of local agricultural production are the most viable options to create sustainable jobs, and therefore reduce high levels of poverty and inequalities. Continued ideological and political dominance of mining capital is in the South African context a curse, because such impacts on the many vital policy positions the state should pursue, particularly its macro-economic policies.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, Political Studies, 2014.